Morphologic and Histologic Comparison of Hypertrophic Scar in Nude Mice, T-Cell Receptor, and Recombination Activating Gene Knockout Mice. Issue 6 (December 2015) - Momtazi, Moein; Ding, Jie; Kwan, Peter; Anderson, Colin C.; Honardoust, Dariush; Goekjian, Serge; Tredget, Edward E.
Abstract : Background: Proliferative scars in nude mice have demonstrated morphologic and histologic similarities to human hypertrophic scar. Gene knockout technology provides the opportunity to study the effect of deleting immune cells in various disease processes. The authors' objective was to test whether grafting human skin onto T-cell receptor (TCR) αβ -/- γδ -/-, recombination activating gene (RAG)-1 -/-, and RAG-2 -/- γc -/- mice results in proliferative scars consistent with human hypertrophic scar and to characterize the morphologic, histologic, and cellular changes that occur after removing immune cells. Methods: Nude TCRαβ -/- γδ -/-, RAG-1 -/-, and RAG-2 -/- γc -/- mice ( n = 20 per strain) were grafted with human skin and euthanized at 30, 60, 120, and 180 days. Controls ( n = 5 per strain) were autografted with mouse skin. Scars and normal skin were harvested at each time point. Sections were stained with hematoxylin and eosin, Masson's trichrome, and immunohistochemistry for anti-human leukocyte antigen-ABC, α-smooth muscle actin, decorin, and biglycan. Results: TCRαβ -/- γδ -/-, RAG-1 -/-, and RAG-2 -/- γc -/- mice grafted with human skin developed firm, elevated scars with histologic and immunohistochemical similarities to human hypertrophic scar. Autografted controls showed no evidence of pathologic scarring. Knockout animals demonstrated a capacity for scar remodeling not observed in nude mice where reductions in α-smooth muscle actin staining pattern and scar thickness occurred over time. Conclusions: Human skin transplanted onto TCRαβ -/- γδ -/-, RAG-1 -/-, and RAG-2 -/- γc -/- mice results in proliferative scars with morphologic and histologic features of human hypertrophic scar. Remodeling of proliferative scars generated in knockout animals is analogous to changes in human hypertrophic scar. These animal models may better represent the natural history of human hypertrophic scar.